REPRESENTASI SAPTA TIMIRA DALAM PALEGONGAN AMBEKING MANUSA DENGAN METODE ANGRIPTA SASOLAHAN - Putu Setyarini (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2023)
Ambeking Manusa is a new creation of Palegongan dance work which was developed according to the changing times. With the advancement of science and technology, human nature begins to shift according to what they see. These phenomena that occur in society are what the stylists put into the art of a Palegongan work entitled Ambeking Manusa. Ambeking means character / behavior while Manusa means human, which means the nature contained in humans. This displays seven human traits that make humans forget themselves, which are commonly called Sapta Timira. Palegongan work is embodiment of the seven human traits that are contained presented in the form dance and seven masks character. Palegongan Ambeking Manusa's theoretical foundation is Angripta Sasolahan theory. This Palegongan Ambeking Manusa work is in the form of a palegongan creation, with seven dancers wearing masks and multimedia to enhance the presenting technique. The gamelan Semar Pagulingan provides the accompaniment. This art contains a message about education, creativity, and morals. Messages for community education on integrity, work ethic, and mutual collaboration. The lesson for creativity in this piece is to be able to work with what you have, including movement, floor patterns, and costumes. The last messag is a moral message that expects humans to avoid traits that cause them to forget themselves and be self-centered, so that they could have a sense of responsibility and like to help others.